The little drummer mouse : a Christmas story - Mayer, Mercer, 1943- (New York : Dial Books for Young Readers, 2006)
A little mouse who is teased for being the smallest and for playing an acorn drum is singled out to give a gift to the very special child who has been born in a nearby stable.
Accelerated Reader AR
Keywords: Jesus Christ -- Nativity -- Juvenile fiction; Mice -- Juvenile fiction; Drummers (Musicians) -- Juvenile fiction; Christmas fiction